Peningkatan Kinerja Keuangan UMKM: Peran Literasi Keuangan, Inklusi Keuangan, Teknologi Keuangan Di Era Digital - Nilamsari, Meysa Ayu; Widiastuti, Anna (Forum Kerjasama Pendidikan Tinggi (FKPT), 2026)
Micro, Small, and Medium Enterprises (MSMEs) play an important role in supporting Indonesia’s economic growth. However, many MSME actors still face challenges in financial management, particularly in terms of financial literacy, financial inclusion, and the utilization of financial technology. This study aims to analyze the effects of financial literacy, financial inclusion, and financial technology on the financial performance of wood carving MSMEs in Jepara Regency. The method used is a quantitative approach with a survey conducted on 200 respondents selected using accidental sampling from a population of 5,327 business units. Data were collected through questionnaires and analyzed using SmartPLS 4. The results show that financial literacy has a positive and significant effect on financial performance, with a coefficient value of 0.298 and a significance level of 0.000. Financial inclusion also has a positive and significant effect, with a coefficient value of 0.170 and a significance level of 0.014. Financial technology has a positive and significant effect, with a coefficient value of 0.230 and a significance level of 0.000. An R-square value of 0.255 indicates that these three variables can explain 25.5% of the variation in MSMEs’ financial performance. These results emphasize the importance of improving financial literacy, expanding access to formal financial services, and utilizing digital technology to support the sustainability and competitiveness of MSMEs.